2006
DOI: 10.1016/j.molstruc.2006.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of caffeine as determined by gas electron diffraction aided by theoretical calculations

Abstract: The molecular structure of caffeine (3,7-dihydro-1,3,7-trimethyl-1H-purine-2,6-dione) was determined by means of gas electron diffraction. The nozzle temperature was 185 °C. The results of MP2 and B3LYP calculations with the 6-31G** basis set were used as supporting information.These calculations predicted that caffeine has only one conformer and some of the methyl groups perform low frequency internal rotation. The electron diffraction data were analyzed on this basis. The determined structural parameters (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Egawa et al determined the structure of the CAFF by gas electron diffraction and theoretical calculations at MP2 and B3LYP levels of theory with the 6-31 g (d,p) basis set. 11 As mentioned, He-I photoelectron spectra for each of the molecules considered in this work (HYP, XAN, and CAFF) have been reported by two separate groups. [5][6][7] For the spectra for HYP recorded by Dougherty et al 7 and Lin et al, 5 differences in 16 to 20 eV binding energy were reported.…”
Section: Introductionmentioning
confidence: 87%
“…Egawa et al determined the structure of the CAFF by gas electron diffraction and theoretical calculations at MP2 and B3LYP levels of theory with the 6-31 g (d,p) basis set. 11 As mentioned, He-I photoelectron spectra for each of the molecules considered in this work (HYP, XAN, and CAFF) have been reported by two separate groups. [5][6][7] For the spectra for HYP recorded by Dougherty et al 7 and Lin et al, 5 differences in 16 to 20 eV binding energy were reported.…”
Section: Introductionmentioning
confidence: 87%
“…These two structures are chosen as representatives, due to the big similarity between them and the rest of the molecules from the both of analyzed groups. The selected calculated bond lengths and angles of 1,3,7‐trimethylxanthine residue in all of the investigated molecules, have been compared with structural parameters of caffeine monohydrate in the crystal21 (Table 1), in accordance with the used atom numbering (Figs. 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…4 according to the method described in 6 ref. [15]. Then the thermal-averaged probability distribution of the angle φ 2 was estimated from the obtained eigenfunctions and energy levels.…”
Section: Analysesmentioning
confidence: 99%
“…g distances with the theoretical r e distances, the differences between them were estimated to be, r g -r e ≈ (3/2)al 2 [15], by using the diatomic approximation [22] and by neglecting the centrifugal distortion term. By assuming the Morse parameter, a, to be 2.0 Å -1 , the term, r g -r e , is estimated to be around 0.006 Å for the C-C bonds in the ring, 0.007 Å for the C-C single bonds, 0.005 Å for the C=C bond, 0.004 Å for the C=O bond and 0.016 -0.018 Å for the C-H bonds.…”
mentioning
confidence: 99%